Evaluation of E-Budgeting Implementation in Provincial Government of DKI Jakarta Using CIPP Model Approach - Rama Andika Thio Rahman; Gugus Irianto; Rosidi Rosidi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2019)
This research aims at analyzing the effectiveness of e-Budgeting implementation with the Provincial Administration of Special Capital Region of Jakarta using the CIPP (Context, Input, Process and Product) model of Stufflebeam (2003). This qualitative research employs a case study approach and collects the data through interview and documentation. The Informants of this research are the Local Government Budget Team (TAPD) of the Special Capital Region of Jakarta Province. The results of this research show that the e-Budgeting implementation with the Provincial Administration of Special Capital Region of Jakarta is worthy to be continued since it evidently runs effectively with regard to the four components of CIPP Model. With regard to Context, it focuses on successful achievement of initial purposes, which are budget transparency and accountability. The finding of context evaluation is a shift of users’ paradigm from old system to e-Budgeting. With regard to Input, it uses adequate facilities and infrastructures as well as human resources, and the results of input evaluation show that an improvement of network and server used is necessary. With regard to Process, it facilitates and minimizes error in RKA arrangement process. The results of process evaluation show that there is no legally applicable SOP in e-budgeting implementation stages. With regard to output (Product), it improves Local Budget quality in case of its appropriateness to RPJMD planning document, and active role of budget control management.